Complete plastome sequence of Pseuderanthemum haikangense C.Y. Wu & H.S. Lo (Acanthaceae): a medicinal plant in South China - Xu Gao; Hong-Xin Wang; Zhi-Xin Zhu; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2020)
Pseuderanthemum haikangense (Acanthaceae) is a shrubs native to Guangdong, Hainan, Yunnan province of China. In this study, we report and characterize the complete plastome sequence of P. haikangense in order to provide genomic resources helpful for promoting its conservation and medicinal utilization. The complete plastome is 152,849 bp in length and contains the typical quadripartite structure of angiosperm, including two Inverted Repeat (IRs) regions of 25,849 bp, a Large Single-Copy (LSC) region of 83,878 bp and a Small Single-Copy (SSC) region of 17,273 bp. The plastome contains 113 genes, consisting of 79 unique protein-coding genes, 30 unique tRNA gene and 4 unique rRNA genes. The overall A/T content in the plastome of P. haikangense is 61.60%. The complete plastome sequence of P. haikangense will provide a useful resource for the conservation and garden utilization of this species as well as for the phylogenetic studies of Acanthaceae.